![x-y=1\\x=1+y........(3) equation](https://img.qammunity.org/2023/formulas/mathematics/high-school/6i6vjo3kva57v0fael26cly7weyk94nn4o.png)
5.I derived the third equation from the second equation therefore I will substitute the above equation x=1+y in the first equation .Mind you to derive the third equation I made x the subject of the equation in the second equation. You can use any equation to derive the third equation. I chose to use the second equation because the variable have the coefficient of 1 so it will be very easier foe me without any divisions to leave the variable independent.
I will substitute the equation x=1+y in the equation -3x+3y=3.
If you derived the third equation from the second equation DO NOT substitute in the equation you derived the new equation from.
![-3(1+y)+3y=3\\-3-3y+3y=3\\-3\\eq 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/wwm8uxqhukmgh65j2cks8ckx6bgcu340qt.png)
as far as I went you can see that there is no solution for the first problem
No solution
6. Substitute y=-x+4 in the equation 2x-3y=3. In the place of y plug in-x+4
![2x-3(-x+4)=3\\\\2x+3x-12=3\\5x=3+12\\5x=15\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/aik344g7l5gf5qr4wav1l544b767ugtibf.png)
![(5x)/(5) =(15)/(5) \\x=3\\\\y=-(3)+4\\y=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/yovkhlameae8x6d05624n5dyq20py2kw0f.png)
Hope this helps